Hubungan Tingkat Pengetahuan Tentang HIV/AIDS Dengan Sikap Remaja Pada Perilaku Seksual Pranikah di Desa Naman Teran Kabupaten Karo Tahun 2023 - Indah Selviana; Herianto Bangun (Universitas Katolik Widya Karya Malang, 2023)
Premarital sexual behavior has many negative impacts, including unwanted pregnancy and the risk of contracting HIV/AIDS. The aim of the research is to determine the relationship between the level of knowledge about HIV/AIDS and teenagers' attitudes towards premarital sexual behavior in Naman Teran Village, Naman Teran District, Karo Regency in 2019. The independent variable is the level of knowledge about HIV/AIDS. The dependent variable is teenagers' attitudes towards premarital sexual behavior. The type of research used in this research is analytical observational with a cross sectional approach. The population was all 160 teenagers in Naman Teran Village, using accidental sampling technique. The sample in this study was 35 people. The types of data used are primary data and secondary data. The statistical test used is the Chi-square test p=0.05. The results of the analysis show that teenagers have sufficient knowledge about HIV/AIDS (54.3%), and a positive attitude towards premarital sexual behavior (74.3%), Chi-square test results p = 0.00 <of <of p=0.05, thus Ho is rejected. Ha is accepted, meaning there is a relationship between the level of knowledge about HIV/AIDS and teenagers' attitudes towards premarital sexual behavior. It is hoped that teenagers in Naman Teran Village will further increase their knowledge about HIV/AIDS with premarital sexual behavior.